MENTAL MAPS ARE INNOVATIONS OF QUALITATIVE MATHEMATICS AND PHYSICS STUDYING - Broslavska, Halyna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The main content of the article is aimed at exploring the mental maps. Defined conditions for the effectiveness of mind maps in the learning process. The use of mental maps allows you to increase students' interest in the material being studied.